The significant development of Chinese traditional ink painting as a new concept in visual communication design - Alli, Hassan (Online Journal of Art and Design, 2024)
Traditional Chinese ink painting has an important milestone in the development of Chinese art history. Recently, most of the new concepts of visual communication design in China was influenced by cultural elements especially the Chinese traditional ink painting. However, how to strengthen the application of Chinese traditional ink painting as a new concept of visual communication has become a challenge. This study aims to investigate the significance of Chinese traditional ink painting as a new concept of visual communication design. A total of 20 respondents were involved in this survey acknowledged as design expert such as designer, professional painters, art artist and scholar. The results highlighted the significant of Chinese traditional ink painting in the development of new concept of visual communication design for better aesthetic appearance as well as for industry relate growth in China.